2023
DOI: 10.1177/12034754231152224
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cryotherapy Combined With Intralesional Purified Protein Derivative (PPD) Versus Intralesional PPD Monotherapy in the Treatment of Multiple Common Warts

Abstract: Introduction Intralesional antigen immunotherapy represents a promising therapeutic approach for the treatment of different types of warts, particularly if multiple and/or recalcitrant. Aim to investigate the efficacy and safety of combined cryotherapy with intralesional purified protein derivative (PPD) immunotherapy in the treatment of multiple common warts. Methods Fifty patients were randomly divided into two groups (25 patients each): Group A: receiving intralesional PPD immunotherapy for the largest wart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Two studies trialed intralesional PPD in the largest wart compared with cryotherapy for all warts plus intralesional PPD in the largest wart and found no significant difference in response rates. However, both found a shortened time to clearance in the combination group ( Awad et al, 2023 ; Ibrahim et al, 2022 ). A combination of IFN alfa-2b with pulsed dye laser had a statistically significant higher clearance rate than either therapy alone ( Choi et al, 2002 ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Two studies trialed intralesional PPD in the largest wart compared with cryotherapy for all warts plus intralesional PPD in the largest wart and found no significant difference in response rates. However, both found a shortened time to clearance in the combination group ( Awad et al, 2023 ; Ibrahim et al, 2022 ). A combination of IFN alfa-2b with pulsed dye laser had a statistically significant higher clearance rate than either therapy alone ( Choi et al, 2002 ).…”
Section: Discussionmentioning
confidence: 87%
“…Wart types most commonly included verruca vulgaris, followed by verruca plantaris and verruca palmaris, and least commonly included verruca plana and periungual warts. Only 4 therapies were trialed in greater than 10 RCTs: these 4 most common therapies were MMR (n = 24), PPD (n = 19), vitamin D (n = 15), and Candida (n = 14) ( Table 3 ) ( Abd-Elazeim et al, 2014 ; Abd El-Magiud et al, 2020 ; Agrawal et al, 2018 ; Ahmed et al, 2020 ; Amin et al, 2021 ; Amirnia et al, 2016 ; Awad et al, 2023 ; Awal and Kaur, 2018 ; Baaniya et al, 2021 ; Bhalala et al, 2021 ; Eldahshan et al, 2022 ; ElGhareeb, 2019 ; El Sayed et al, 2020 ; Elsayed Ghaly et al, 2021 ; Fathy et al, 2019 ; Fawzy et al, 2020 ; Hodeib et al, 2021 ; Ibrahim et al, 2022 , 2020 ; Jain and Marfatia, 2021 ; Jartarkar et al, 2021 ; Kareem et al, 2019 ; Kaur et al, 2021 ; Khozeimeh et al, 2017 ; Khurshid and Pal, 2009 ; Mehta et al, 2021 ; Milante et al, 2019 ; Mohammed et al, 2021 ; Mohta et al, 2022 , 2021 ; Nassar et al, 2022 ; Nofal et al, 2022a , 2022b , 2022c , 2021a , 2021b , 2020b ; Nofal and Nofal, 2010 ; Rageh et al, 2021 ; Rajegowda et al, 2020 ; Rezai et al, 2019 ; Rutnin et al, 2023 ; Shaldoum et al, 2020 ; Wan Ahmad Kammal et al, 2021 ; Zamanian et al, 2014 ; Zainab et al, 2021 ). The most common therapy, MMR, was reported in 807 patients across studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a growing body of evidence, mainly from clinical experience, has shown cryotherapy to be an excellent second line treatment in the protocols when the initial agent application is unsuccessful (94). A study by Awad et al (95) has shown that adding N 2 cryotherapy prior to intralesional (IL) antigen immunotherapy is a promising therapeutic approach in multiple and recalcitrant warts. It works on the principle of the effector immune cells attraction to HPVloaded keratinocytes, highlighting the safety and efficacy of the combination therapy with the potential of reducing the number of treatment sessions.…”
Section: Cryotherapymentioning
confidence: 99%